A method for fixing and paraffin embedding tissue to retain the natural fluorescence of reporter proteins. (January 2017) - Nakagawa, Akifumi; Alt, Kate Von; Lillemoe, Keith D.; Castillo, Carlos Fernández-del; Warshaw, Andrew L.; Liss, Andrew S.
Protocol Summary: Here we present an ethanol fixation protocol that allows for the direct visualization of the natural fluorescence of reporter proteins while maintaining excellent tissue histology. We demonstrate the utility of this method for visualizing green and red fluorescent proteins in a wide range of murine tissues using both cytoplasmic and membrane-localized fluorescent reporter proteins. Tissues fixed by this method also allow for immunohistochemical studies, providing a single method to visualize the natural fluorescence of reporter proteins with subsequent detection of cellular proteins.